Operation-Aware System Design for Synergistic Integration of Regenerative Braking Energy of Railway Systems into EV Fast Charging Stations - Sepehr Najafilarijani; Seyed Saeed Fazel; Mokhtar Bozorg; Hamed Jafari Kaleybar (IEEE Access, 2023)
Fast charging stations (FCSs) for electric vehicles are associated with large power demands, often coinciding with peak power demands from other consumers. This places significant strain on distribution networks (DNs). To address this issue, this paper proposes a promising method that harnesses the untapped potential of electric railway systems (ERSs) and wasted regenerative braking energy (RBE) of trains in combination with a battery energy storage system (BESS) to supply EV charging station and participate in the FCS energy supply chain (FCS-ESCH). The proposed integrated approach, as the intermodal sustainable electric transportation system (SETS), aims to reduce the peak power demand of FCSs especially at strategic locations, such as parking areas close to electric railway stations and park-and-ride areas. To achieve this goal, an operation-aware optimization model is developed that determines the optimal sizes of the interfacing converter and the BESS, while also proceeding with optimal energy exchange planning. A generic model for trains’ RBE production is proposed, as well, and adapted to the operation-aware optimization model to verify the effectiveness of the proposed approach by conducting simulations of a real case study that accurately replicates system behavior with the desired level of precision. Furthermore, sensitivity analyses are performed to explore the impact of varying the power rating of the interfacing converter responsible for transmitting RBE to the FCS-ESCH, as well as the per-unit price of BESS energy capacity. The results showcase the potential of employing SETS as an efficient means to mitigate the challenges associated with FCSs, especially peak shaving and cost reductions, paving the way for a more sustainable electric transportation system.